ANALISIS KEMAMPUAN SISWA DALAM MENYELESAIKAN SOAL CERITA MATEMATIKA DI SMP KARTIKA VIII-1 JAKARTA - Yosua Yosua; Indra Martha Rusmana (LPPM Universitas Bina Bangsa, 2021)
This study aims to determine the ability of students in solving math story problems at SMP Kartika VIII-1. Another objective is to analyze the students' ability to solve math story problems at SMP Kartika VIII-1. The method used to analyze the ability is a qualitative method by collecting data through a story question test to describe the student's ability to solve story questions. The ability to understand story problems with a very high category, the ability to plan strategy solving strategies for story problems with a sufficient category, the ability to implement a strategy for solving story problems with a high category, and the ability to prove the truth of the results with a low category